circNUDT21 promotes bladder cancer progression by modulating the miR-16-1-3p/MDM2/p53 axis - Liang Chen; Wencheng Li; Zhiqin Li; Yarong Song; Jun Zhao; Zhaohui Chen; Gallina Kazobinka; Lulu Li; Yifei Xing; Teng Hou (Elsevier, 2021)
Bladder cancer (BC) is a common genitourinary malignancy. This study investigated the regulatory effects of an exonic circRNA, circNUDT21, in the progression of BC. The circNUDT21 level was overexpressed in BC tissues and cell lines as compared to normal controls. Overexpression and silencing of circNUDT21 promoted and inhibited, respectively, the proliferative and invasive abilities of BC cells. Mechanistical analysis showed that circNUDT21 acted as a miR-16-1-3p sponge and that MDM2 was a potential downstream target of miR-16-1-3p. We further verified that overexpression of circNUDT21 was associated with elevated MDM2 and reduced p53 expression. CircNUDT21 promoted BC progression by acting as a sponge of miR-16-1-3p to activate the miR-16-1-3p/MDM2/p53 axis. These findings suggest that circNUDT21 functions as an oncogenic circRNA and may be a potential therapy target for BC.